2018
DOI: 10.1038/s41467-017-02636-4
|View full text |Cite
|
Sign up to set email alerts
|

Engineering human pluripotent stem cells into a functional skeletal muscle tissue

Abstract: The generation of functional skeletal muscle tissues from human pluripotent stem cells (hPSCs) has not been reported. Here, we derive induced myogenic progenitor cells (iMPCs) via transient overexpression of Pax7 in paraxial mesoderm cells differentiated from hPSCs. In 2D culture, iMPCs readily differentiate into spontaneously contracting multinucleated myotubes and a pool of satellite-like cells endogenously expressing Pax7. Under optimized 3D culture conditions, iMPCs derived from multiple hPSC lines reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
304
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 271 publications
(321 citation statements)
references
References 59 publications
14
304
3
Order By: Relevance
“…The availability of human pluripotent stem cells and methods for their directed myoblast differentiation will facilitate the translation of the reported rat to a human model. In fact, alternative models of engineered human skeletal muscle using the forced expression of Pax7 or directed multi‐lineage differentiation in induced pluripotent stem cells have recently been reported. These advances will be important for applications in screens for regeneration inducing compounds and studies of cell based muscle repair.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of human pluripotent stem cells and methods for their directed myoblast differentiation will facilitate the translation of the reported rat to a human model. In fact, alternative models of engineered human skeletal muscle using the forced expression of Pax7 or directed multi‐lineage differentiation in induced pluripotent stem cells have recently been reported. These advances will be important for applications in screens for regeneration inducing compounds and studies of cell based muscle repair.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ability to engineer a biomimetic 3D muscle environment in vitro could overcome several limitations of traditional 2D cell culture systems. [103] As discussed below, 3D muscle cultures permit far longer culture times, [9,104,105] increased myotube size, [106] increased protein content, [106] and improved maturation of myosin heavy chain (MHC) gene expression compared to 2D cultures. [104] Importantly, engineered muscles enable the measurements of contractile function (i.e., muscle strength and fatigue resistance), which are more representative of in vivo muscle physiology and pathology than the sole changes in protein or gene expression, as typically assessed in 2D cell cultures.…”
Section: Current Skeletal Muscle Tissue Engineering Methodsmentioning
confidence: 99%
“…[103] As discussed below, 3D muscle cultures permit far longer culture times, [9,104,105] increased myotube size, [106] increased protein content, [106] and improved maturation of myosin heavy chain (MHC) gene expression compared to 2D cultures. [104] Importantly, engineered muscles enable the measurements of contractile function (i.e., muscle strength and fatigue resistance), which are more representative of in vivo muscle physiology and pathology than the sole changes in protein or gene expression, as typically assessed in 2D cell cultures. For a utility in preclinical drug development, 3D tissue-engineered muscle should: 1) be prepared from human cells, 2) replicate the structure, function, and regenerative capacity of native muscle, 3) accurately model phenotype of various congenital and acquired diseases, and 4) be amenable to iniaturization and online functional and metabolic monitoring for enhanced experimental throughput.…”
Section: Current Skeletal Muscle Tissue Engineering Methodsmentioning
confidence: 99%
“…Myogenic cells have been derived from iPSCs via genetic reprogramming or addition of small molecules. Studies have reported that iPSC derived myogenic cells can fuse with existing myofibers following in vivo transplantation and can also generate three‐dimensional (3D) functional skeletal muscle in vitro . The breadth of lineages in which iPSCs differentiate through allows for a variety of cell types (neural, vascular, and muscular) to populate these 3D tissue constructs .…”
Section: Stem Cells For Skeletal Muscle Regenerationmentioning
confidence: 99%
“…The breadth of lineages in which iPSCs differentiate through allows for a variety of cell types (neural, vascular, and muscular) to populate these 3D tissue constructs . These functional tissue constructs were able to survive, vascularize, and function when transplanted in vivo, suggesting that the can replace damaged or dysfunctional muscle . Additionally, these constructs can be used for disease modeling and drug screening applications …”
Section: Stem Cells For Skeletal Muscle Regenerationmentioning
confidence: 99%